The Johnstown flood : an Up2U historical fiction adventure - Mullarkey, John, 1963-; Mullarkey, Lisa.; Martin, Dana, 1985- (Minneapolis, Minn. : Magic Wagon, 2014)
On May 31, 1889, as the waters rise in Johnstown, Pennsylvania, Sarah Beth, her mother, and Vincent, a boy she likes, struggle to save what they can from the flooding but when the dam collapses the reader is invited to choose between three possible endings for Sarah Beth and her family.
5.9
3-6
Keywords: Dam failures -- Pennsylvania -- Johnstown (Cambria County) -- History -- 19th century -- Juvenile fiction; Floods -- Pennsylvania -- Johnstown (Cambria County) -- History -- 19th century -- Juvenile fiction; Johnstown (Cambria County, Pa.) -- History -- 19th century -- Juvenile fiction; Floods -- Pennsylvania -- Johnstown (Cambria County) -- History -- 19th century -- Fiction; Johnstown (Cambria County, Pa.) -- History -- 19th century -- Fiction; Plot-your-own stories; Historical fiction; Floods -- Johnstown (Cambria County, Pa.) -- History -- Fiction; Johnstown (Cambria County, Pa.) -- History -- Fiction; Plot-your-own stories; Historical fiction; Historical fiction